2008
DOI: 10.1590/s0036-36342008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Factores pronósticos relacionados con la supervivencia del cáncer de mama

Abstract: These results give consistency to diagnostic and therapeutic criteria for women with breast cancer who receive medical attention in Mexico, taking into consideration the characteristics of the tumor -such as extension, clinical stage and status of the lymph nodes- before making a decision as to the initial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
2
12
0
8
Order By: Relevance
“…The lowest survival corresponds to stages IIIB (47.5%), IIIA (44.2%) and IV (15%). 43 A similar result was found in the Spanish study, in which the diagnosis of breast cancer was more frequent in stage II (42%) and the survival at five years was 95%. Women diagnosed at early stages have higher percentages of survival.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…The lowest survival corresponds to stages IIIB (47.5%), IIIA (44.2%) and IV (15%). 43 A similar result was found in the Spanish study, in which the diagnosis of breast cancer was more frequent in stage II (42%) and the survival at five years was 95%. Women diagnosed at early stages have higher percentages of survival.…”
Section: Resultssupporting
confidence: 83%
“…46 The epidemiological data encountered indicated that the highest incidence for breast cancer is in the age group of 50 and 60 years, followed by the age group 40 to 49. 3,20,39,43 Thus, this reaffirms the necessity of conducting mammography examinations from the age of 50, as established by the International Consensus for the Control of Breast Cancer, 47 and the Brazilian initiative, which instituted mammography for all women from the age of 40 approaching this reality. This initiative was enacted by Law 11.664/08, which made effective healthcare actions that ensure the prevention, detection, treatment and monitoring of the cancers of the cervix and breast, in the context of the Brazilian National Health System (SUS), with this initiative, anticipation mammography for 40 year olds, being contrary to the international consensus.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations